Transient Unilateral Parotid Gland Swelling Following Upper Endoscopy / Chieng Jin Yu ...[et al.] - Chieng, Jin Yu; Then, Ru Fah; Shahabudin, Sharifah Intan Safura; Pan, Yan (Universiti Teknologi MARA Cawangan Selangor, 2021)
Transient parotid gland swelling could happen as complication after per oral endoscopy or intubation. We reported a 53-year-old man who developed transient unilateral parotid gland swelling following esophagogastroduodenoscopy (OGDS) with dilatation of achalasia cardia. The swelling of the parotid gland was transient and resolved completely without any intervention.